Guided Aspiration for Determining the Microbiological Aetiology of Aortic Vascular Graft and Endograft Infections. (December 2021) - Ljungquist, Oskar; Dias, Nuno; Haidl, Sven; Sonesson, Björn; Sörelius, Karl; Ahl, Jonas
Abstract : Objective: Open and endovascular aortic repair may be complicated by aortic vascular graft or endograft infection (VGEI). Confirming the microbiological aetiology is a key element in providing the best available treatment to patients with a VGEI. The primary aim of this study was to describe the technique of direct aneurysm sac guided aspiration (DASGA) in determining the microbiological aetiology in a cohort of patients with VGEIs, and to report its diagnostic value. Methods: This was a retrospective observational single centre study performed between the years 2011 to 2020 in Malmö, Sweden. Patients with a suspected aortic VGEI, where a DASGA was performed at the Vascular Centre, were included in the study. Results: In total, 31 guided aspirations were performed in 27 patients (25 male [93%]; median age 77 years [range 57 – 82 years]). The combination of culture and 16S rRNA/18S rRNA gave a microbial aetiology in 25/31 (81%) DASGAs. Importantly, excluding three cases where infection was ruled out, this rate increases up to 89%. A polymicrobial aetiology was found in six (24 %) cases. The most common bacteria found were Cutibacterium spp. ( n  = 8) and Listeria monocytogenes ( n  = 4) . In total, the dominant aetiology could be further characterised into normal gut flora ( n  = 12; 48%) or skin commensals ( n  = 8; 32%). No patients had persistent morbidity related to the DASGA. Conclusion: DASGA can be used successfully to determine the microbiological aetiology of open and endovascular graft infections. This method appears to be safe, with a high success rate for confirming the microbiological aetiology of VGEIs, particularly if standard culturing methods are combined with 16S rRNA/18S rRNA. Finding the causative microbial aetiology is crucial, and in the vast majority of cases translumbar puncture can be used without serious complications.